NATO and American security - Knorr, Klaus, 1911-1990 (Princeton legacy library., 1959)
The Berlin crisis, the Suez intervention, the Cyprus problem, and other differences among the NATO powers have tended to weaken the alliance in the face of constant Soviet pressure. Emphasizing the 1960's, a group of experts here examines the future of NATO and American security: military strategy for limited and large scale war, the problem of deterrence, nuclear sharing, surprise attack and disarmament, the special positions of England and Germany, and alternatives to NATO. The contributors are: Klaus Knorr, Roger Hilsman, C. E. Black, F. J. Yeager, G. W. Rathjens Jr., Malcolm Hoag, M. A. Kaplan, A. L. Burns, T. C. Schelling-, Denis Healey, G. A. Craig, and P. H. Nitze.Originally published in 1959.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.